تنفيذ البرنامج الإعدادي لمسابقة قراءة الكتب في معهد سومطرى طواليب بارابك بوكيت تينجي - Rahmi, Hafizatur; Zamani , Athira Fakhriatuz; Latifi, Lutfia Nasrul (Sekolah Tinggi Ilmu Tarbiyah Ibnu Sina Malang, 2023)
The purpose of this study was to describe implementation of the Musabaqah Qiro'atul Pole program at the Sumatra Thawalib Islamic Boarding School Parabek Bukittinggi, West Sumatra in preparing students to prepare for Qiroatul Pole competitions in various competitions, to improve quality in reading Arabic books and to preserve the culture in Islamic boarding schools that we know is identical with the study of classic books and so that we can maintain and develop the basic values of students, especially at the Sumatra Thawalib Parabek Islamic boarding school, Bukittinggi, West Sumatra. This study used a qualitative approach with a case study type. Data collection techniques were in the form of interviews and documentation, as well as data sources in the form of documents and informants related to extracurriculars, especially MQK Takhassus. The results of this study are that the Sumatra Thawalib Parabek Islamic Boarding School, Bukittinggi, West Sumatra runs the Takhassus MQK Program which is guided by a special coach by carrying out the Takhassus MQK program every day, which provides preparations for students to take part in competitions.